2015
DOI: 10.1051/0004-6361/201323136
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of ETV diagrams as diagnostic tools for long-term period variations

Abstract: Context. The credibility of an eclipse timing variation (ETV) diagram analysis is investigated for various manifestations of the mass transfer and gravitational radiation processes in binary systems. The monotonicity of the period variations and the morphology of the respective ETV diagrams are thoroughly explored in both the direct impact and the accretion disk mode of mass transfer, accompanied by different types of mass and angular momentum losses (through a hot-spot emission from the gainer and via the L2/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…Often the characteristic time scale of the phenomenon substantially exceeds the entire period of human EB observations. Gen-erally in each such case, the ETVs are manifest as a slow, constant-rate variation of the orbital period which results in a quadratic O − C pattern (for analytic descriptions of the ETVs induced by some of the listed effects see Nanouris et al 2011Nanouris et al , 2015. Shorter time-scale physical ETVs can arise, e.g., from magnetic activity (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Often the characteristic time scale of the phenomenon substantially exceeds the entire period of human EB observations. Gen-erally in each such case, the ETVs are manifest as a slow, constant-rate variation of the orbital period which results in a quadratic O − C pattern (for analytic descriptions of the ETVs induced by some of the listed effects see Nanouris et al 2011Nanouris et al , 2015. Shorter time-scale physical ETVs can arise, e.g., from magnetic activity (see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A general discussion is given in [109], while many studies concerning the (O-C) diagrams of various stars can be found in [110]. Moreover, the efficiency of (O-C) diagrams as diagnostic tools for long-period variations have been examined [111,112], too.…”
Section: The Construction Of An (O-c) Diagrammentioning
confidence: 99%
“…As investigated by Gokhale et al (), Nanouris et al (), and Dervişoğlu et al (), we express the rate of change of spin angular momentum of the accretor and donor, respectively, as: J˙spin,normalaJorb=()q+1rrM˙aMd and J˙spin,normaldJorb=q()q+1rrM˙dMd. …”
Section: Basic Dynamical Evolution Equations Of Orbitmentioning
confidence: 99%